Nosocomial infections in emergency cesarean sections at the Maternal Perinatal Institute 1996. - Meza, Luis (2015)
To determine the rate of hospital emergency cesarean infection and possible predisposing factors. DESIGN: Epidemiological study of transversal, retrospective and descriptive. PLACE: Maternal Perinatal Institute, Lima, Peru. MATERIALS AND METHODS: Patients seen between January and June 1996 and had nosocomial infection criteria. RESULTS: 10962 births were Caesarean sections 2784 (25.4%), of which 421 had nosocomial infection cases (15.1%). The most common site of surgical wound infection was followed by endometritis and urinary tract infection. The infection occurred in 25% of children under 19 years, by 9% in those over 35 years, 56% of nulliparous, between 37 and 42 weeks gestation (82%), with inadequate prenatal care at 74%. CONCLUSIONS: It was found that around 50% of interventions in the morning presents nosocomial infections, there being increased infections shortening or lengthening the operative time.